Що робить дизайн персонажів гарним - Зіноватна, Д. В. (ХНУРЕ, 2020)
The question of what makes a character design good is perhaps one of the most controversial, obscure and subjective. Characters are used everywhere, not only in games, it is literature, advertising, the film industry and more. And the same character, for different spheres, will change dramatically. What design we (the person) will be more strongly attached to, is directly related to what personality we will attach to, and it will also change, but from one person to another.
Keywords: дизайн персонажів; персонаж